Influence Of Problem Based Learning (Pbl) Model On Increasing Students' Knowledge Of Functional Food Processing Systems - aftah simah bengi; Rina Febriana; Rusilanti Rusilanti (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the effect of the application of the Problem Based Learning (PBL) model on improving students' knowledge on the material of functional food processing systems at SMAN 5 Tangerang Regency. The PBL stages carried out include problem orientation, organization for learning, investigation guidance, presentation of results, evaluation of problem solving carried out in 2 meetings. The research method applied is quantitative through a quasi-experimental design with a nonequivalent control group type. The sample was divided into two class groups, namely the experimental class and the control class through a purposive sampling technique with the basic criteria of classes with the same average academic value. The data collection applied was a test instrument with a multiple choice of 20 questions. Based on the results of the descriptive test, the experimental class's score was higher than the control class. This finding was strengthened by a paired sample t-test statistical test which obtained a sig value <0.05 which stated that PBL learning increased students' knowledge. The results of the independent t-test obtained a sig value of 0.000 <0.05. These results indicate a significant difference between the post-test results of students in the experimental class and the control class. The N-Gain Score calculation also showed an increase of 59.75% in the experimental class and 23.98% in the control class. Based on these results, it can be concluded that the PBL model is moderately effective in improving students' knowledge of functional food processing systems. Therefore, the results of this study can be used as input for educators in efforts to improve student knowledge through the use of the PBL model in classroom learning.